Assessment of reef fish abundance and biomass in the Pujada Bay corridor of Davao Oriental for marine protected area management - Eballe, Ariel C. (2014)
The five Marine protected areas (MPA) covered by this study are located in the barangays of Luban, Lanca and Lawigan in Mati City; Barangay San Ignacio in Manay; and Barangay Jovellar in Tarragona. Fish visual census was used to determine reef fish abundance and biomass inside the MPAs. The same assessment was also done in representative sites outside of the MPAs for comparison. Of the five sites, Barangay Luban MPA has the best reef fish assemblage, having moderate fish abundance and high fish biomass. On the other hand, Barangay Lanca has the lowest fish abundance and biomass among the sites. Target species have comprised most of the biomass inside the MPAs except in Barangay Lanca and San Ignacio, wherein non-target species contributed more to the biomass. It was also in these two areas that abundance and biomass outside the MPAs were higher than inside. It is hoped that effective management efforts of these MPAs will solve the present problem of low stocks and improve the assemblage, abundance, and biomass inside the MPAs including as well the outside marine reserves through spillover effect.
Keywords: Reef fishes; Fish biomass; Pujada Bay (Davao Oriental); Mindanao studies